The myosin regulatory light chain Myl5 localizes to mitotic spindle poles and is required for proper cell division. Issue 2 (8th March 2021) - Ramirez, Ivan; Gholkar, Ankur A.; Velasquez, Erick F.; Guo, Xiao; Tofig, Bobby; Damoiseaux, Robert; Torres, Jorge Z.
Abstract: Myosins are ATP‐dependent actin‐based molecular motors critical for diverse cellular processes like intracellular trafficking, cell motility, and cell invasion. During cell division, myosin MYO10 is important for proper mitotic spindle assembly, the anchoring of the spindle to the cortex, and positioning of the spindle to the cell mid‐plane. However, myosins are regulated by myosin regulatory light chains (RLCs), and whether RLCs are important for cell division has remained unexplored. Here, we have determined that the previously uncharacterized myosin RLC Myl5 associates with the mitotic spindle and is required for cell division. We show that Myl5 localizes to the leading edge and filopodia during interphase and to mitotic spindle poles and spindle microtubules during early mitosis. Importantly, depletion of Myl5 led to defects in mitotic spindle assembly, chromosome congression, and chromosome segregation and to a slower transition through mitosis. Furthermore, Myl5 bound to MYO10 in vitro and co‐localized with MYO10 at the spindle poles. These results suggest that Myl5 is important for cell division and that it may be performing its function through MYO10.